PEMILUKADA DAN PROBLEMA TATA KELOLA PEMERINTAHAN YANG BAIK - Permana, Yogi Setya (Jurnal Penelitian Politik, 2010)
Pemilukada is an instrument to develop local good governance Local election creates a spacefor democraticdevelopment that includes strengthening ofcivil society economic and cultural The assumption here is that goodgovernance is able to transform deepening democracy into deepeningprosperity This review discusses evaluationofPemilukada process and its obstacles